Tourism competitiveness in small island developing states - Roland Craigwell (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The tourism industry is the leading segment of the services industries in small island developing states (SIDS). This paper therefore seeks primarily to investigate both the nature and determinants of tourism competitiveness in SIDS. Judging from the various calculated indices of tourism competitiveness, the competitive position of tourism in SIDS is a major issue. More specifically, SIDS are still price uncompetitive and appear to be losing ground in the global tourism market. There is also a need for these countries to improve their levels of investment for the development of the technological infrastructure (telecommunications technology), and more importantly to ensure that the economic gains from tourism are spread to the lower-income households. Additionally, the findings of this study highlight some difficulties (from a macroeconomic perspective) of designing appropriate policies and strategies to enhance tourism competitiveness in SIDS. In particular, price and income considerations, given their predominantly exogenous nature, are not easy to control, but nevertheless must be explicitly taken into account in any policy aimed at improving tourism competitiveness.
Keywords: L83; F0; O1; 330; competitiveness; tourism; SIDS; Tourismuswirtschaft; Insel; Kleines-Land-Modell